THE CONCEPTUAL SIGNIFICANCE OF PROVERBS IN UZBEK AND ENGLISH CULTURAL WORLD (Journal of Universal Science Research, 2025)
Proverbs are a fundamental part of cultural heritage, carrying wisdom, ethical values, and the worldview of different societies. This article examines the conceptual significance of proverbs in Uzbek and English cultures, analyzing their role in transmitting values, beliefs and historical traditions. A comparative analysis of proverbs from both cultures reveals similarities in moral teachings and differences influenced by social structures and historical developments. The study also explores the evolution of proverbs in modern contexts, assessing their relevance in contemporary society.